2012
DOI: 10.1007/s00339-012-6910-x
|View full text |Cite
|
Sign up to set email alerts
|

Drilling rate of five metals with picosecond laser pulses at 355, 532, and 1064 nm

Abstract: Experimental results on picosecond laser processing of aluminum, nickel, stainless steel, molybdenum, and tungsten are described. Hole drilling is employed for comparative analysis of processing rates in an air environment. Drilling rates are measured over a wide range of laser fluences (0.05-20 J/cm 2 ). Experiments with picosecond pulses at 355 nm are carried out for all five metals and in addition at 532 nm, and 1064 nm for nickel. A comparison of drilling rate with 6-ps and 6-ns pulses at 355 nm is perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Le Drogoff et al [31] determined the ablation threshold of aluminum thin films for plasma formation to be approximately 0.1 J cm À2 by subpicosecond laser pulses. Le Harzic et al [32] and Spiro et al [18] carried out the experimental studies on micromachining pure aluminum by ultrafast laser pulses to obtain the ablation thresholds at low energy-density and the values were calculated to be about 0.12 and 0.46 J cm À2 , respectively. The numerical values are not the same, and they also cannot satisfy the demand of various kinds of aluminum alloy in ultrafast laser micromachining.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Le Drogoff et al [31] determined the ablation threshold of aluminum thin films for plasma formation to be approximately 0.1 J cm À2 by subpicosecond laser pulses. Le Harzic et al [32] and Spiro et al [18] carried out the experimental studies on micromachining pure aluminum by ultrafast laser pulses to obtain the ablation thresholds at low energy-density and the values were calculated to be about 0.12 and 0.46 J cm À2 , respectively. The numerical values are not the same, and they also cannot satisfy the demand of various kinds of aluminum alloy in ultrafast laser micromachining.…”
Section: Introductionmentioning
confidence: 99%
“…So far, ultrafast pulsed laser ablation thresholds of several typical materials have been investigated. In the aspect of metal materials, many studies have focused on stainless steel, gold, silver, copper, platinum, tungsten, chromium, niobium, molybdenum, nickel, nickel-base alloy, titanium, and titanium alloy [13][14][15][16][17][18][19][20][21][22][23][24]; however, ablation mechanisms and thresholds of aluminum and its alloys have not been extensively investigated, and the available few studies on aluminum and its alloys generally focused on the micro-nanostructure characteristics of ultrafast laser processing, laser-induced breakdown spectroscopy, and laser shock peening on pure aluminum or aluminum alloy. Jorgensen et al [25] formed the nanoparticles using femtosecond laser ablation in intermetallic aluminum-nickel (NiAl) alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Nanosecond laser technology is widely adopted in the industry for micromachining (based on time and cost-effectiveness) [9,10]. With regards to most adequate laser wavelength for metal micromachining, it must be taken into account that the absorption coefficient of metals is generally higher in the UV range compared to that in the IR region, which should provide a lower ablation threshold for UV pulses [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several singlepulse ablation studies for metals have already been reported for pulse durations from ns-to fs-pulses [11][12][13][14][15][16][17][18][19][20][21][22] . Furthermore a multitude of studies exhibited the influence of multi-laser pulses to different materials [3,5,17,18,[23][24][25] . However, those studies concentrated on reporting the influence of multi-laser pulses for a large number of pulses from 10 up to several of 100.…”
Section: Introductionmentioning
confidence: 99%